2020
DOI: 10.1002/anie.202006350
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Computational Investigation of Bright Orange‐Emitting Benzothiadiazole [10]Cycloparaphenylene

Abstract: Conjugated aromatic macrocycles are attractive due to their unique photophysical and optoelectronic properties. In particular, the cyclic radially oriented π‐system of cycloparaphenylenes (CPPs) gives rise to photophysical properties unlike any other small molecule or carbon nanomaterial. CPPs have tunable emission, possess large extinction coefficients, wide effective Stokes shifts, and high quantum yields. However, accessing bright CPPs with emissions beyond 500 nm remains difficult. Herein, we present a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 61 publications
0
54
0
1
Order By: Relevance
“…25,[28][29][30] Therefore, we chose [10]CPP as the main scaffold for this study as it has previously shown a high tolerance to strain based reactivity. 20,[23][24][25] The optimized ground state geometry, absorbance, optimized excited state geometry, and uorescence of each nanohoop was calculated. The trends observed in the uorescence were rationalized using supporting evidence from StrainViz and NICS calculations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25,[28][29][30] Therefore, we chose [10]CPP as the main scaffold for this study as it has previously shown a high tolerance to strain based reactivity. 20,[23][24][25] The optimized ground state geometry, absorbance, optimized excited state geometry, and uorescence of each nanohoop was calculated. The trends observed in the uorescence were rationalized using supporting evidence from StrainViz and NICS calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, [10]CPTcaq exhibits intramolecular charge transfer (ICT), which is responsible for decreasing the quantum yield. 25 [10]CPTcaq is a donor-acceptor molecule where the HOMO and LUMO of the S 1 0 are separated. While the uorescence is dramatically red-shied, the quantum yield decreases by 92% to 0.05.…”
Section: Observed Optoelectronic Properties Related To Computational mentioning
confidence: 99%
See 3 more Smart Citations